1989
DOI: 10.1002/ar.1092250305
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular system of the newborn marsupial cat Dasyurus hallucatus

Abstract: The ultrastructure of the ear of the newborn native cat was examined to determine whether the vestibular system contained sensory receptors. A sensory region, presumably the utricle, was identified in each ear and consisted of a discrete population of otoliths overlying a sensory epithelium which possessed kinocilia and stereocilia. The remainder of the vestibular system did not appear to be developed anatomically. The newborn cat has rudimentary vestibular, olfactory, and mechanoreceptors (Merkel cells), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Likewise, a saccule was not observed in any of the stages examined. Similar observations have been reported in the newborn of D. hallucatus, a carnivorous Australian mar supial [Gemmell and Nelson, 1989]. In both species, Dasyunis and Didelphis, only one sensory region could be identified, the macula of the utricle.…”
Section: Discussionsupporting
confidence: 67%
“…Likewise, a saccule was not observed in any of the stages examined. Similar observations have been reported in the newborn of D. hallucatus, a carnivorous Australian mar supial [Gemmell and Nelson, 1989]. In both species, Dasyunis and Didelphis, only one sensory region could be identified, the macula of the utricle.…”
Section: Discussionsupporting
confidence: 67%
“…It has been suggested that vestibular guidance is involved (Cannon, Bakker, Bradshaw, McDonald, & McDonald, 1976). Indeed, the utriculus component of the vestibular apparatus, but not the sacculus or semicircular canals, has all the structural elements necessary for functioning (Gemmell & Nelson, 1989). The trigeminal sys-tem has some sensorimotor and olfactory functioning at birth (Hughes & Hall, 1988;Nelson, 1988), and may also be involved in guiding the neonate on its trek to the pouch.…”
Section: Order Of Appearance Of Righting Systemsmentioning
confidence: 99%
“…The otocyst, as has been described in Gemmell and Nelson (1989), is similar to stage 15 eutherian embryos where the cochlea and vestibular regions are apparent, where the endolymphatic appendage is a diverticulum of the vestibular region and where there is an indication of the formation of one of the semicircular canals from the vestibulary region. The vomeronasal organ has begun to develop but nerves have not yet reached the brain.…”
Section: Internal Featuresmentioning
confidence: 56%
“…Even though there are olfactory receptors (Gemmell and Nelson 1988c) there is no organisation within the telencephalon or diencephalon to enable a connection to a motor centre. The newborn thus depends on the trigeminal, facial, vestibular [see Gemmell and Nelson 1989], glossopharyngeal, vagus, accessory and hypoglossal but not auditory. Thus the only senses that the newborn can use are touch, thermal, balance and chemical (via trigeminal).…”
Section: Discussionmentioning
confidence: 99%